The role of the Triple islands (Greater Tunb, Lesser Tunb and Abu Musa) in Iran’s Maritime supremacy in the Persian Gulf - ali amiri; hojat naderi (تحقیقات کاربردی علوم جغرافیایی)
For many coastal countries, maritime supremacy has always been a major concern of their grand strategies. The existence of islands is one of the most important means to acquisition of maritime supremacy in maritime territories. Iran, Due to its maritime position, has many islands in the Persian Gulf, the most important of which are the Triple  islands (Greater Tunb, Lesser Tunb and Abu Musa). The political issue of the United Arab Emirates' claim to the islands and their very strategic position has made these islands very important in the Persian Gulf maritime supremacy. Therefore, the analysis of how these islands affect Iran's maritime supremacy is considered as the main issue of this paper. Here, the method of data collection is library and documentary. Then, the collected data were analyzed by qualitative- inferential method. The results show that the Triple  islands in various ways have expaned the Iranian maritime supremacy and have helped to stabilization Iran's maritime supremacy in the Persian Gulf and the Strait of Hormuz. These islands have increased  the Iran’s Maritime supremacy by extension Iran's maritime sovereignty under international maritime law and the FIR line, located adjacent to the Hormuz International Waterway, defination maritime traffic Corridors, and playing the role of Warship in Iran's naval navy.